DYNAMICS OF HALAL PRODUCT ASSURANCE REGULATION: A COMPARATIVE ANALYSIS OF THE LEGAL STRUCTURES OF INDONESIA AND THAILAND - Aulia, Rizki; Koto, Ismail (JCH (Jurnal Cendekia Hukum), 2025)
Halal product assurance regulations are an important issue in the development of the global halal industry, especially for countries seeking to strengthen consumer protection while increasing the competitiveness of their products in the international market. This study aims to analyze the dynamics of halal certification regulations in Indonesia and compare them with the halal certification system in Thailand. The research method used is normative legal research with a legislative and comparative approach. Research data was obtained through a literature study of relevant legislation, scientific literature, and policy documents, then analyzed qualitatively using a descriptive-analytical method. The results show that Indonesia implements a compliance-oriented halal regulation model through Law Number 33 of 2014 concerning Halal Product Guarantee, which is reinforced by Law Number 11 of 2020 concerning Job Creation and Law Number 6 of 2023. This regulation changed the halal certification system from voluntary certification to mandatory certification, involving BPJPH as the state administrative authority, MUI as the halal fatwa issuer, and the Halal Inspection Agency as the technical audit institution. In contrast, Thailand implements a more flexible and market-oriented model, where halal certification is legally voluntary but in practice becomes de facto mandatory due to export market demands. Thailand's halal system is managed by the Central Islamic Council of Thailand (CICOT) and reinforced through the integration of scientific approaches such as the concept of Halal Science and the Halal-Q system, which combines halal standards with international food safety standards. This difference in regulatory paradigms shows that Indonesia emphasizes legal certainty through state regulation. At the same time, Thailand places more emphasis on market competitiveness and the integration of halal standards with global quality systems.